The Essence of Academic Performance - Nchindila, Bernard; Corrigan, Trudy (IntechOpen, 2020)
This volume is a collection of research on academic performance. Chapters cover such topics as targeting underserved urban youth, education and science, community-based projects, pedagogy, and developing educational programs, among others. Written by experts, this book offers a comprehensive view of recent developments in the field of academic performance.